Chemical Constituents of Hedyotis diffusa and Their Anti-Inflammatory Bioactivities - Hsin-Yi Hung; Kun-Ching Cheng; Ping-Chung Kuo; I-Tsen Chen; Yue-Chiun Li; Tsong-Long Hwang; Sio-Hong Lam; Tian-Shung Wu (MDPI AG, 2022)
Seven new anthraquinones with rare 2-isopropyldihydrofuran (1-3) and 2,2-dimethylpyrano (4-7) moieties together with thirty-four known compounds were isolated from the extracts of whole Hedyotis diffusa plants. Their structures were elucidated and established by various spectroscopic and spectrometric analytical methods. Among these isolates, selected compounds were examined for their anti-inflammatory activity. The results showed that rare substituted anthraquinones displayed potent inhibitory activity with IC50 values ranging from 0.15 ± 0.01 to 5.52 ± 1.59 µM on the N-formyl-methionyl-leucyl-phenylalanine/cytochalasin B (fMLP/CB)-induced superoxide anion generation and elastase release cellular models. Meanwhile, the proposed drug target of the active anthraquinone was studied by computer modeling. The binding affinity between the anti-inflammatory anthraquinone and elastase was evaluated by molecular docking. These results provided the scientific insight into the medicinal values of Hedyotis diffusa and vision of development as lead compounds.